Correcting spellings in second language learners' computer-assisted collaborative writing. Issue 1 (2nd January 2016) - Musk, Nigel
Abstract : The present study uses multimodal conversation analysis to examine how pupils studying English as a foreign language make spelling corrections in real time while doing collaborative computer-assisted project work. Unlike most previous related investigations, this study focuses on the process rather than evaluating the final product . The findings establish how the initiation and correction of (perceived) spelling errors involve varying configurations of three agents: the pupil currently typing, the other pupil and the computer software. Almost 80% of spelling corrections are carried out by the pupil typing with no intervention from the other pupil or the spellchecker. It is argued that here both the 'triadic ecology' and the timing of correction trajectories entail a structural preference for self-correction, which in turn reduces the affordances of the spellchecker and collaboration. Nevertheless, the spellchecker and the other pupil do play a role in catching potential misspellings that the typist has missed. Moreover, rather than right-clicking to activate the spellchecker's menu of spelling suggestions, the typist typically deletes back to before the faulty letter(s) and then re-types words, which suggests the importance of progressivity of the typing flow as well as no need for the spellchecker's assistance.